SEJARAH PERKEMBANGAN HADIS DI MESIR - Reshinta, Eka Bella; Nur Rahmawati, Tri Buana Eka; Muhid (AL-ATSAR: Jurnal Ilmu Hadits, 2025)
This study explores the development of Hadith studies in Egypt, an essential center of Islamic scholarship since the early Islamic period. It focuses on Egypt’s strategic position as a bridge connecting three continents and begins with the arrival of Islam in the 7th century under Amr bin Ash. The primary focus is the evolution of Hadith traditions in Egypt, including contributions from scholars such as Imam At-Tahawi, Ibn Hajar Al-Asqalani, and Laits bin Sa’ad. Secondary aspects cover the influence of educational institutions like Al-Azhar and other figures who advanced Hadith studies. The research aims to highlight Egypt’s role as a key center for Hadith studies and analyze the factors sustaining its scholarly traditions. Using a qualitative descriptive approach, data were gathered from historical literature, biographies of scholars, and influential Hadith works. The findings show that Egypt has been a crucial center for Hadith development, supported by scholarly contributions and lasting academic traditions, with Al-Azhar and the Amr bin Ash Mosque playing significant roles. Keywords: Egypt, Islam, Hadith, Development